2015
DOI: 10.1111/all.12808
|View full text |Cite
|
Sign up to set email alerts
|

Aggravation of airway inflammation and hyper‐responsiveness following nasal challenge with Dermatophagoides pteronyssinus in perennial allergic rhinitis without symptoms of asthma

Abstract: House dust mite nasal provocation test induces and aggravates both upper and lower airway inflammation and hyper-responsiveness in patients with persistent allergic rhinitis without asthmatic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
(29 reference statements)
1
16
0
Order By: Relevance
“… 36 37 38 In our previous work, we found that the nasal lavage eosinophil count correlated with sputum eosinophil count, FeNO, FEV1%, and PD 20 6 hours after NPT. 15 Similarly, in the current study, we found that sputum eosinophil count was significantly correlated with nasal lavage eosinophil count in non-AIT subjects both at baseline and after 6 hours of NPT. However, there was no correlation between upper and lower eosinophilic inflammation in AIT subjects at any AIT time point, regardless of whether measurements were taken before or after 6 hours of NPT.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“… 36 37 38 In our previous work, we found that the nasal lavage eosinophil count correlated with sputum eosinophil count, FeNO, FEV1%, and PD 20 6 hours after NPT. 15 Similarly, in the current study, we found that sputum eosinophil count was significantly correlated with nasal lavage eosinophil count in non-AIT subjects both at baseline and after 6 hours of NPT. However, there was no correlation between upper and lower eosinophilic inflammation in AIT subjects at any AIT time point, regardless of whether measurements were taken before or after 6 hours of NPT.…”
Section: Discussionsupporting
confidence: 82%
“… 14 We have previously reported that NPT can increase lower airway eosinophilic inflammation in AR patients without asthma symptoms. 15 Although it is reported that the nasal response to NPT is attenuated after AIT, it remains unknown whether it could decrease lower airway inflammation triggered by NPT.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with allergic rhinitis induced by mites, but without asthma, nasal provocation with the allergen produced a significant increase in blood, nasal secretions and induced sputum eosinophils, with a simultaneous worsening of the BHR to methacholine and pulmonary function . This fact adds further evidence for the existence of a pathophysiological connection between BHR and inflammation in rhinitis.…”
Section: Lower Airway Inflammatory Involvement In Rhinitismentioning
confidence: 75%
“…Inflammatory signs in the lower airway were demonstrated in patients with AR without concurrent asthma symptoms …”
Section: Lower Airway Inflammatory Involvement In Rhinitismentioning
confidence: 99%
“…39 Another study demonstrated that HDM nasal challenge tests cause initiation and exacerbation of airway inflammation and hyper-responsiveness in both upper and lower airways in patients with persistent AR without asthmatic symptoms. 40 Climate change contributes to increases in chemical air pollutant and aeroallergen production and their distribution. 33,36,41,42 Climate change affects vegetation, resulting in changes in the start, duration, intensity, and distribution of allergenic pollen.…”
mentioning
confidence: 99%